Personal factors related to self-care management among people with hypertension at primary health care: A cross-sectional study - Anggraini Dwi Kurnia; Sri Hariyati; Nur Melizza; Chairul Huda Al Husna; Anchaleeporn Amatayakul; Adelia Handoko (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: Hypertension requires long-term treatment and can last a lifetime. Recommendations for hypertensive patients, where it is necessary to change behavior related to self-care, consist of increasing a healthy diet, limiting sodium intake, increasing physical activity, reducing smoking, and reducing alcohol consumption.